Anatomy, hydraulic and physical indexes of Gliricidia sepium (Jacq.) Steud. wood - Quintanar-Isaías, Alejandra; Ángeles, Guillermo; Zavala-Hurtado, José Alejandro (Instituto de Ecología, A.C., 2016)
An anatomical, physical and physiological study of the heartwood and sapwood of Gliricidia sepium ( Jacq.) Steud. was carried out using six trees collected during the rainy and dry seasons in a dry forest from Veracruz, México. Stem segments were cut at 1,30 m above the ground for obtaining wood samples for macroscopic and microscopic observations, and for the water content and specific gravity analyses. Following classical microtechnique procedures and international classifications and nomenclatures for describing microscopic features, wood samples and permanent slides of wood sections and dissociated material were made. Estimations of vulnerability and collapse indexes, and K h-theoretical were made from vessel diameter, vessel number and effective vessel area. Analysis of variance and principal components analysis showed that some fiber, vessels, rays and pit features influenced differences among trees, sites and seasons. Although variability of those features is relatively low, it would explain the sapwood and heartwood stability during changes in the hydric regime caused by dryness and rain. Collapse and mvulnerability indexes, as well as K esomorphic xylem quite vulnerable h show ato embolisms, but with high success to develop in disturbed environments. This could be explained by the presence of tyloses, abundant axial parenchyma and high values of specific gravity that assure resistance of fiber and vessel cell walls to collapse.